Gawai dan Ibu Muda : Studi Pola Asuh Ibu Muda pada Anak di Dusun Karanganyar - m muadi (Cakrawala: Jurnal Kajian Manajemen Pendidikan Islam dan studi sosial, 2020)
Social media is a source of information that can change all aspects of human life. This is inseparable from technological developments that have penetrated womenfolk, especially young mothers. Among young mothers, social media is considered superior in the speed of interaction, all information can be easily obtained. Not only that, social media is also a special space for young mothers to share experiences. Not even a few then consider it a contemporary label for the sake of maintaining prestige. The view of society sees women who are still dominated in all respects by men. For women, social media is a means to prove that women can actualize themselves well. So that social inequality towards men can be overcome, women are active in social media and there is no direct control given by parents, there are efforts to control given by parents. In limiting the behavior of gadget players that are not in accordance with the values ​​and norms in society.